Influence of different light-curing units in surface roughness and gloss of resin composites for bleached teeth after challenges - Carvalho Andrade, Karina [UNESP]; Pavesi Pini, Nubia Inocencya; Dias Moda, Mariana [UNESP]; de Souza e Silva Ramos, Fernanda [UNESP]; dos Santos, Paulo Henrique [UNESP]; Fraga Briso, André Luiz [UNESP]; Cestari Fagundes, Ticiane [UNESP] (Elsevier, 2020)
The aim of this study evaluates the surface roughness and gloss of resin composites for bleached teeth, using different modes of light curing and photoinitiators after challenges. Eighty discs were made with Filtek Z350XT (camphorquinone) and Vit-l-escence (camphorquinone, amine and lucerin-TPO). Forty disks were light cured by a monowave LED and forty with a polywave LED. Roughness and gloss analysis were made. The specimens were exposed to brushing and hydrochloric acid (HCl) and analyzed again. The data were analyzed by two-way ANOVA analysis of variance for repeated measures, considering each challenge separately. Afterwards, Tukey test was applied for multiple comparisons (p ≤ 0.05). All resins had a significant increase in roughness after brushing with polywave device and only Vit-l-escence presented significant increased after HCl. Regarding the surface gloss, no influence on light-curing units was found for all resins after toothbrushing and after HCl for Vit-l-escence. All resins showed significant decrease in gloss after the challenges. The type of LED device did not influence the roughness and surface gloss of resin composites for bleached teeth after the challenges.
Keywords: Composite resins; Curing lights; Photoinitiators